Analisa Pengaruh Kecepatan Kendaraan terhadap Tingkat Kebisingan yang Terjadi pada Ruas Jalan dengan Perkerasan Kaku - Syahrul, Syahlendra; Zakaria, Aisyah (INTEK: Jurnal Penelitian, 2019)
Along with the increasing needs of people inMakassar city for the mode of transportation, the number of thegrowth of motor vehicles that operate on the road becomes largerthan the growth of the number of roads built. This has causedsome problems in the transportation sector. In addition tocongestion problems, problems arise from road surface damagedue to increasing traffic loads that must be borne by the roadsurface. To anticipate this, some strategic streets in the city ofMakassar then designed by using a rigid pavement that hasgreater strength in carrying the burden. Another problem thatarises from the growing number of motor vehicles that operateon the road is greater than the growth of the number of roadsbuilt is the higher levels of noise pollution or traffic noise. Noise issourced from the sound of a vehicle engine and the frictionbetween the vehicle tire and the road surface. So that roads withrigid surface pavement surfaces that have a rougher surfacetexture, potentially lead to higher noise levels. This study aims todetermine how much noise levels that occur in roads that userigid pavement in the city of Makassar. The road segments, suchas Jl. Abd. Dg. Sirua, Jl. Batua Raya and Jl. Adhyaksa. The toolused to measure traffic noise is the Sound Level Meter (SLM).The survey was conducted for 1 day for each of the roadsegments reviewed. The data taken are the level data of flatnessof road surface, vehicle speed data and traffic noise level data.Data processing is done by analyzing the relationship between thefactors that affect the noise with the noise level that occurs on theroad with rigid pavement. The results of this study are expectedto provide information about how big the effect of vehicle speedon the noise level that arises on the road with rigid pavement.Keyword--Noise; speed of vehicle; Rigid Pavement